Clinicoepidemiological spectrum of connective tissue diseases in the pediatric population in a tertiary care center in North India: A cross-sectional observational study - Dharitree Senapati; Vibhu Mendiratta; Anu Maheshwari; Vidya Yadav; Taru Garg; Yusufa Ahmed (Wolters Kluwer Medknow Publications, 2024)
Background: Connective tissue diseases (CTDs) are chronic in nature and carry a high risk of morbidity, disability, and mortality if not recognized and treated promptly. Data on clinical spectrum of CTDs in the pediatric age group are sparse from developing countries such as India. Objective: To study the clinicoepidemiological spectrum of CTDs in the pediatric age group. Methodology: A hospital-based, cross-sectional, observational study was undertaken over a period of 16 months from January 2021 to June 2022 in the dermatology outpatient department and pediatric rheumatology clinic in a tertiary care hospital in North India. Clinical and laboratory findings were recorded. Results: A total of 100 children diagnosed with a CTD were included in the study. The mean age was 11.11 ± 4.20 years. Out of 100 children, 55% were female and 45% were male with a male-to-female ratio of 1:1.2. Our study included 63% juvenile idiopathic arthritis, 17% systemic lupus erythematosus, 7% juvenile dermatomyositis, 6% Kawasaki disease, 3% systemic sclerosis, and 2% Henoch-Schonlein purpura and mixed CTD patients each. Mucocutaneous features commonly seen were rash (40%), oral ulcers (22%), and photosensitivity (18%). Commonly seen systemic features were joint pain (77%), followed by fever (63%). Conclusion: Mucocutaneous manifestations are frequently seen in CTDs and constitute a frequent and an early manifestation of CTD. Early recognition of CTD in the pediatric age group will help in timely initiation of treatment to prevent disabilities and mortality.